Protocol for a mixed methods process evaluation of a hybrid implementation-effectiveness trial of a scaled-up whole-school physical activity program for adolescents: Physical Activity 4 Everyone (PA4E1) - Mclaughlin, Matthew (Trials, 2020)
BACKGROUND: Physical Activity 4 Everyone (PA4E1) is a physical activity program for secondary schools located in low-socioeconomic areas. Over a 24-month period, schools in the program arm of a cluster randomised controlled trial (n = up to 38 schools) will receive a multi-component implementation support strategy to embed the seven school physical activity practices of the PA4E1 program. This article describes the process evaluation of the PA4E1 hybrid implementation-effectiveness trial. The process evaluation aims to describe the fidelity and reach of the implementation support strategies using quantitative data; and to describe the acceptability, appropriateness and feasibility of the implementation support strategies and physical activity practices to school stakeholders using mixed methods. METHODS: Quantitative and qualitative data will be collected from participants (Physical Education teachers, in-School Champions, students) in the program arm. Data collection will involve semi-structured interviews, focus groups, a fidelity monitoring log, a fidelity checklist, surveys, and routinely collected administrative and website data. Quantitative data will be analysed descriptively and qualitative data will be analysed thematically within and across data sets. Triangulation between data sources will be used to synthesise findings regarding the implementation and potential mechanisms of impact of PA4E1 on school physical activity practice adoption, with respect to context. DISCUSSION: Results of the process evaluation will facilitate the interpretation of the findings of the trial outcomes. It will comprehensively describe what was actually implemented and identify the potential contribution of the various components of the implementation support strategy to the school physical activity practice adoption outcomes. Findings will inform future improvement and scale-up of PA4E1 and approaches to implementing secondary school-based physical activity programs more broadly. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry ACTRN12617000681358 registered 12 May 2017.